Edukasi Konseling Kesesuaian Pemakaian Kontrasepsi Pada TIM Penggerak PKK Kabupaten Muaro Jambi - Lia Nurdini; Asparian; Puspita Sari; Sri Astuti Siregar (Jurnal Salam Sehat Masyarakat (JSSM), 2022)
Increased Unmed Need Contraception is a problem that is of concern because it will increase unwanted pregnancies which will have an impact on the health of mothers and children. Muaro Jambi Regency is the Regency with the highest unmet need for contraception in Jambi Province at 14.54% and the trend in the use of contraception is very dominating, namely pills and injections at 85.8%, which if leftunchecked will have an impact on increasing the unmed need for contraception which is even higher. This community service activity has the aim of increasing the knowledge and counseling skills of the PKK Mobilization Team in Muaro Jambi Regency in providingappropriate information regarding the suitability of contraceptive use to guide the community to make the rightdecisions in rational contraceptive use. Thereare several methods used during providing education, namely lectures,discussions and counseling assistance. This service was carried out at the Muaro Jambi Regency Village Empowerment Office with a target number of 30 PKK mobilizing teams. The results of this community service activity show that there is a significant difference in the knowledge of PKK cadres in the suitability of using contraceptives compared to before participating in mentoring (test score from 78.3 to 86.3). The application of education and counseling on the suitability of contraceptive use needs to be carried out on an ongoing basis as aneffort to improve family planning services by using rational contraceptive use.